The study of lasing properties of rhodamine 6g in solutions of polymer-coated silver nanoparticles - Zeinidenov, A. K.; Аimukhanov A. K.; Ibrayev, N. Kh.; Kudaibergenov, S. E. (Recent Contributions to Physics, 2014)
We studied the lasing characteristics of Rhodamine 6G in the presence of polymer-coated silver nanoparticles. Synthesis of the polymer-coated silver nanoparticles was carried out in a aqueous alcohol solution. As the stabilizer and reducing agent the hydrophilic polymer poly-N-vinylpyrrolidone (PVP, SigmaAldrich) was used. The size of silver nanoparticles is equal to 40-50 nm. Stimulated emission of Rhodamine 6G molecules in aqueous alcohol solution of PVP with a concentration of dye equal to 10-3 mol/l was obtained in the long-wavelength fluorescence band upon photoexcitation with second harmonic of Nd:YAG laser gen= 532 nm, Еimp = 90 mJ, τ = 10 ns in the transversely form. Ascertained that the power density of the pump source 10 MW/cm2 observed lasing spectrum of the dye Rhodamine 6G in solution of PVP at a wavelength equal to λgen = 566 nm. When added to a solution of the dye-polymer-coated silver nanoparticles observed increase in intensity and a narrowing of the laser line. Furthermore, the presence of polymer-coated silver nanoparticles lowers the threshold level of generation.